On dogs and dying : inspirational stories from hospice hounds - Rivera, Michelle A. (New directions in the human-animal bond., 2010)
"This book presents a series of real-life tales of the positive effects dogs have had on people at the end of their lives, chronicling the visits by two therapy dogs, Woody and Katie, to patients in a south Florida hospice facility."--Page 4 of cover